1955
DOI: 10.1172/jci103057
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Urinary Creatine in Progressive Muscular Dystrophy 1

Abstract: In an earlier communication (1) an experiment was described in which the isotopic compositions of urinary creatine and creatinine excreted by a patient with progressive muscular dystrophy were studied after a feeding of glycine-N'5. It was found, that in the first few days urinary creatine was much more enriched with N'5 than was urinary creatinine, and that the isotope concentration in the creatine fell far more rapidly than did that in the creatinine. These results were taken to mean that the creatinuria, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1956
1956
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 3 publications
2
17
0
Order By: Relevance
“…Benzoate loading probably explains why hippurate glycine was less highly labeled than oxalate in the present studies, whereas in the studies of Crawhall and associates (25) free glycine (and presumably hippurate also) was more highly labeled than was oxalate. Finally, the studies reported herein offer additional evidence for the existence of multiple metabolic pools of glycine in poor equilibrium one with another, as previously suggested by studies of a number of other workers (14,27,28).…”
Section: Physiological Disposition Of Oxalate In Mansupporting
confidence: 82%
See 1 more Smart Citation
“…Benzoate loading probably explains why hippurate glycine was less highly labeled than oxalate in the present studies, whereas in the studies of Crawhall and associates (25) free glycine (and presumably hippurate also) was more highly labeled than was oxalate. Finally, the studies reported herein offer additional evidence for the existence of multiple metabolic pools of glycine in poor equilibrium one with another, as previously suggested by studies of a number of other workers (14,27,28).…”
Section: Physiological Disposition Of Oxalate In Mansupporting
confidence: 82%
“…Urinary hippuric acid was isolated according to Quick (13) and purified by treatment with Darco and by repeated recrystallizations from hot water (14). The The cumulative incorporation of C14 into urinary oxalate (Figure 2) ranged from 0.027 to 0.081 per cent (mean, 0.051 per cent) of the administered dose of glycine 1-C14 in five control subjects.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…If this is also true for man, a decrease in the N'5 concentration of urinary creatinine would indicate a dilution of body creatine with unlabeled creatine. However, Roche and Benedict and their associates (18,19) found that the N15 concentration of urinary creatine was much higher than that of urinary creatinine even when the N15 concentration of urinary creatinine was decreasing. These two observations appear to be contradictory, unless it is assumed that the source of urinary creatine is different from the source maintaining tissue concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…A similar defect in the muscular metabolism of creatine occurs in vitamin E-deficient animals (9,17) which also exhibit muscular weakness and wasting, but the primary change in creatine metabolism in progressive muscular dystrophy in man is thought to be a decreased total uptake of creatine because of the smaller muscle mass (18,19). Since the latter might be interpreted as indicating normal metabolism of creatine by the surviving skeletal muscle, it should be pointed out that some of the observations in patients with progressive muscular dystrophy suggest that the changes in creatine metabolism are similar to the changes found in dystrophic mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation